A Novel Construction of Substitution Box Based on Polynomial Mapped and Finite Field With Image Encryption Application - Abid Mahboob; Muhammad Asif; Imran Siddique; Aysha Saleem; Muhammad Nadeem; Dariusz Grzelczyk; Jan Awrejcewicz (IEEE Access)
In the modern block cipher, the substitution box (S-box) is a nonlinear constituent that plays a substantial role to create the confusion in ciphertext. S-boxes with low value of differential uniformity and high value of nonlinearity are considered more secure against cryptanalysis attacks. For the construction of $8× 8$ S-boxes, an efficient and novel scheme is presented in this paper. This scheme based on polynomial mapped and finite field which work only for even integers without multiple of 4 in the range (2-254). Firstly, we take a quadratic polynomial mapped for the construction of S-box from the newly designed map. To keep the S-box bijective, swap each missing entries with repeating entries after that we acquire the initial box. Secondly, to increase the randomness of initial S-box special permutations of symmetric group S256 used and generated the proposed S-box. Lastly, to examine the validity of the suggested S-box we used various tests such as nonlinearity (NL), bit independence criteria (BIC), strict avalanche criteria (SAC), differential uniformity (DU) and linear approximation probability (LAP) which all certify algebraic properties of S-box. Moreover, the features of newly constructed S-box compared with recent S-boxes from literature which show superior performance against intruders’ attacks. Further, S-box is utilized in image encryption scheme and apply MLC (majority logic criterion) and histogram analysis to examined the encryption quality. Our results shows that proposed S-box based encryption scheme is very good as compared to other encryption methods.